Stable Acoustic Pulling in Two-Dimensional Phononic Crystal Waveguides Based on Mode Manipulation - Yanyu Gao; Yongyin Cao; Tongtong Zhu; Donghua Tang; Bojian Shi; Hang Li; Wenya Gao; Yanxia Zhang; Qi Jia; Xiaoxin Li; Rui Feng; Fangkui Sun; et al. (Photonics, 2023)
Acoustic manipulation is a set of versatile platforms with excellent manipulation capabilities. In recent years, researchers have increasingly achieved specific manipulations beyond the translation and capture of particles. Here, we focus on the acoustic field momentum mechanism that generates an acoustic radiation force (ARF). A phononic crystal (PC) waveguide is established to amplify the forward momentum of the acoustic beam through the mode conversion of the acoustic field. Based on the conservation of momentum, the object gains reverse momentum. Thus, acoustic pulling can be achieved through the mode conversion of the acoustic field. Furthermore, we analyze the ARFs of two identical objects. It turns out that they can be manipulated separately by opposing forces. Our study provides a new way to achieve stable long-range acoustic pulling, and will explore, beneficially, the interaction between acoustic waves and matter.